Successful management of a child with bronchoesophageal fistula associated with other anomalies - B V Raghunath; Kavya Angadi; A V Gurudutt; Nidhi Srinivas; L Manjunath; S D Madhu (Wolters Kluwer Medknow Publications, 2023)
Bronchoesophageal fistulas (BEFs) are rare malformations characterized by abnormal communication between the bronchus and the esophagus. Herein, we report a successful management of a child with BEF discovered as an intraoperative surprise and associated with the short gut, annular pancreas, and disorder of intestinal fixation.